Latin America Copes with Volatility, the Dark Side of Globalization - World Bank (Washington, DC, 2014)
Latin American and Caribbean (LAC) region were bumping against capacity constraints with unemployment reaching historically low levels and economic activity hitting bottlenecks and central banks were thus engaged in combating upward price pressures through tighter monetary policies. The focus of attention was, as a result, shifting towards the longer-term growth and equity agendas in what appeared to be a more tranquil global environment. This LAC region continues on a relatively robust growth path after a remarkable performance in the aftermath of the global financial crisis. In effect, as discussed in our April 2011 report "LAC success put to the test," the region's recession in 2009 was relatively short lived and surprisingly mild compared to other middle-income countries (MICs) and to its own past and its recovery in 2010-2011 strong. This report starts by setting the stage on the external environment. It provides an overview of recent economic developments and the prospects for the LAC region in coming months, including an analysis of the sources of external risks for the region.